1997
DOI: 10.1046/j.1420-9101.1997.10040641.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of sex allocation in Mimulus (Scrophulariaceae)

Abstract: Theoretical models of the evolution of resource allocation patterns to male and female function make the assumption that there are inherent trade-offs between the two. Here we use a quantitative genetic approach to quantify trade-offs between male and female function and to determine whether plant populations could readily respond to natural selection by quantifying the amount of genetic variation for pollen and ovule production. Both intra-and interspecific crossing designs were applied to two populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 75 publications
5
64
0
3
Order By: Relevance
“…Characteristics of the studies (number of populations, whether h 2 or r g were reported) are also noted in Table A1. Carr and Fenster (1994), Fenster and Carr (1997), Mossop et al (1994), Ritland and Ritland (1996), Robertson et al (1994) Genetic constraints on floral evolution T-L Ashman and CJ Majetic…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the studies (number of populations, whether h 2 or r g were reported) are also noted in Table A1. Carr and Fenster (1994), Fenster and Carr (1997), Mossop et al (1994), Ritland and Ritland (1996), Robertson et al (1994) Genetic constraints on floral evolution T-L Ashman and CJ Majetic…”
Section: Discussionmentioning
confidence: 99%
“…Values are ranked from the smallest to the largest. n Number of individuals studied, r correlation coefficient ties, such as pollen grains (e.g., Stanton and Young 1994), may be compensated by the effects of genes that control the acquisition of resources (Houle 1991), which can eliminate or reverse genetic correlations between competing entities (e.g., Young et al 1994;Fenster and Carr 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The most widespread of the selfing taxa, M. nasutus, produces reduced, often cleistogamous flowers. Where M. guttatus and M. nasutus co-occur, potential premating barriers to hybridization include differences in microhabitat and flowering time (Martin and Willis 2007) as well as differences in floral morphology (Ritland and Ritland 1989), pollen production (Fenster and Carr 1997), and pollen tube growth (Diaz and MacNair 1999) associated with their different mating systems. Despite these barriers to mating, hybrids are observed at low frequency at many sympatric sites, and there is evidence of recent local introgression at nuclear loci (Sweigart and Willis 2003).…”
Section: Methodsmentioning
confidence: 99%